Undergrading and understaging in patients with clinically insignificant prostate cancer who underwent radical prostatectomy - Oliveira,Irai S. (2010)
PURPOSE: The aim of our study is to evaluate the undergrading and understaging rates in patients with clinically localized insignificant prostate cancer who underwent radical prostatectomy. MATERIALS AND METHODS: Between July 2005 and July 2008, 406 patients underwent radical prostatectomy for clinical localized prostate cancer in our hospital. Based on preoperative data, 93 of these patients fulfilled our criteria of non-significance: Gleason score < 7, stage T1c, PSA < 10 ng/mL and percentage of affected fragments less than 25%. The pathologic stage and Gleason score were compared to preoperative data to evaluate the rate of understaging and undergrading. The biochemical recurrence free survival of these operated insignificant cancers were also evaluated. RESULTS: On surgical specimen analysis 74.7% of patients had Gleason score of 6 or less and 25.3% had Gleason 7 or greater. Furthermore 8.3% of cases showed extracapsular extension. After 36 months of follow-up 3.4% had biochemical recurrence, defined by a PSA above 0.4 ng/mL. CONCLUSIONS: Despite the limited number of cases, we have found considerable rates of undergrading and understaging in patients with prostate cancer whose current definitions classified them as candidates for active surveillance. According to our results the current definition seems inadequate as up to a third of patients had higher grade or cancer outside the prostate.